Arquitectura autóctona de los dènè del río Mackenzie (Canadá) - Junquera Rubio, Carlos (Diputación Provincial de Valladolid: Fundación Joaquín Díaz, 2021)
This essay is grouped in a group of studies in honor of José Luis Alonso Ponga, professor of the area of anthropology at the University of Valladolid (Spain). As a teacher, researcher and scholar, he has devoted much time and effort to traditional architecture in various areas of Spain and mainly the Douro and Sil rivers. I understand that the best gift I can give you is to capture the traditional architecture of a remote area, but close to many of our common reasons for study. This essay focuses on the family residence of the Dèné Indians settled along the Mackenzie River. Este ensayo se agrupa en un conjunto de estudios en honor a José Luis Alonso Ponga, profesor del área de antropología en la Universidad de Valladolid (España). Como docente, investigador y estudioso, ha dedicado mucho tiempo y esfuerzos a la arquitectura tradicional en diversas áreas de España y principalmente de los ríos Duero y Sil. Entiendo que el mejor regalo que puedo hacerle es plasmar la arquitectura tradicional de una zona lejana, pero cercana a muchos de nuestros motivos comunes de estudio. Este ensayo se centra en la residencia familiar de los indios dènè asentados a lo largo del río Mackenzie.